Empowering KDS and ODHA Through Batik-Making Occupational Therapy as an Anticipation of Discrimination and Stikma in the Blitar Greater Community - winarni, sri; Martiningsih, wiwin; Rachmawati, Dewi (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
The quality of life of ODHA will be affected by various problems including stigma and discrimination from society which becomes a double burden for people with HIV/AIDS. Stigma is a negative view that is attached to a person that comes from the environment. Negative stigma and discrimination from society will make the condition of HIV/AIDS sufferers worse, the body continues to decline because it has to work hard as a breadwinner. As an alternative that can be used as leverage to increase productivity, KDS provides skills as a provision for their lives, namely making batik which is developed through Cap and canting, has a contribution of domestic products and from local wisdom as a characteristic of Indonesia, which can increase regional contributions and is in demand by all levels of society. The KDS and ODHA empowerment program through batik-making work therapy has proven successful in increasing the knowledge and skills of participants, where most participants showed increased knowledge and practical skills in making batik. Through these skills, KDS members can produce quality products that can be marketed and contribute to the local economy. This program also shows a positive impact in reducing stigma and discrimination against ODHA in the Blitar Raya community, by creating a new and positive social identity. With the right sustainability strategy, this empowerment can make a long-term contribution to improving the welfare of ODHA and encouraging better social acceptance in society.